Anaemia: A Risk factor for Preterm Labour - MARIAM MALIK, MAHWISH NAJAM, KIREN KHURSHID MALIK (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine whether or not anaemia is a risk factor for preterm labour. Study design: Case control study Place and duration of study:This study was conducted in the Department of Obstetrics and Gynaecology Unit I, Sir Ganga Ram Hospital/Fatima Jinnah Medical College, Lahore from April 2013 to September 2013. Patients and methods: Three hundred and forty patients presenting in labour and fulfilling the inclusion criteria were included in this study. Patients were divided into two groups A and B. Each group had 170 patients. Patients with gestational age between 28-36 weeks were assigned to group A (case group) and those with gestation more than 37 weeks assigned to group B (control group). Detailed history was taken from the patients of both groups. In order to check hemoglobin level, venous blood sample from patients of both groups was collected. Results: Total of 340 patients were enrolled in this study. In group A (cases) 56% and in group B (control) 42.4% were from age group between 18-25 years. The odds of having preterm birth were 1.724 times greater in patients having age between 18-25 years as compared to the patients who were more than 25 years (p<0.05). The cases had statistically significantly less mean haemoglobin level as compared to controls(cases=7.50, controls=9.69. P value <0.05). Conclusion:It is concluded from this study that anaemia is strongly associated with preterm labour.